2016
DOI: 10.2119/molmed.2016.00063
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Overexpression of Hemopexin Inhibits Inflammation and Vascular Stasis in Murine Models of Sickle Cell Disease

Abstract: Sickle cell disease (SCD) patients have low serum hemopexin (Hpx) levels due to chronic hemolysis. We hypothesized that in SCD mice, hepatic overexpression of hemopexin would scavenge the proximal mediator of vascular activation, heme, and inhibit inflammation and microvascular stasis. To examine the protective role of Hpx in SCD, we transplanted bone marrow from NY1DD SCD mice into Hpx -/-or Hpx +/+ C57BL/6 mice. Dorsal skin fold chambers were implanted 13 wks post-transplant, and microvascular stasis (% nonf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 77 publications
0
44
0
1
Order By: Relevance
“…This was recently confirmed in a study of SCD patients correlating high plasma hemoglobin levels appreciated as an additional important mediator of inflammation and vascular injury (102,103). In sickle cell mice, free heme drives inflammation, vaso-occlusion, and coagulation that are blocked by the heme scavenger hemopexin (104)(105)(106)(107)(108)(109). In cultured cells, heme promotes secretion of high levels of placenta growth factor (110), which in turn induces release of the potent vasoconstrictor endothelin 1 (111), a common mediator of PH.…”
Section: Evidence Linking Cell-free Hemoglobin To Scd Complicationsmentioning
confidence: 76%
“…This was recently confirmed in a study of SCD patients correlating high plasma hemoglobin levels appreciated as an additional important mediator of inflammation and vascular injury (102,103). In sickle cell mice, free heme drives inflammation, vaso-occlusion, and coagulation that are blocked by the heme scavenger hemopexin (104)(105)(106)(107)(108)(109). In cultured cells, heme promotes secretion of high levels of placenta growth factor (110), which in turn induces release of the potent vasoconstrictor endothelin 1 (111), a common mediator of PH.…”
Section: Evidence Linking Cell-free Hemoglobin To Scd Complicationsmentioning
confidence: 76%
“…Nevertheless, Hx, but not HSA, was effective at preventing tissue injury and inflammation in mouse models of hemolysis (5,(36)(37)(38)(39). Previous reports have also shown that hepatic overexpression of Hx inhibits inflammation and vascular stasis in murine SCD (40), while Hx -/mice develop a severe renal damage after experimental hemolysis. This points to Hx as a guardian of kidney function during intravascular hemolysis (41).…”
Section: Discussionmentioning
confidence: 87%
“…The major function of Hx appears to be neutralization and scavenging of excess free heme from the circulation. Up-take of heme-Hx complexes in the liver (Potter et al, 1993) is mediated via the scavenger receptor low-density lipoprotein receptor-related protein-1 (LRP1, synonymous with CD91) (Hvidberg et al, 2005; Vercellotti et al, 2016). Hx belongs to the acute-phase reactants, which include a number of plasma proteins such as C-reactive protein, α2-macroglobulin and α1-antitrypsin that are up-regulated in the liver as part of a systemic inflammatory response (Heinrich et al, 1990; Baumann and Gauldie, 1994).…”
Section: Protection Against Heme Toxicity Via Hemopexin and The Heme mentioning
confidence: 99%